6 Crete: Early Iron Age to Classical. (November 2022) - Kotsonas, Antonis
Abstract : This review covers recent archaeological work on Early Iron Age to Classical Crete, focusing on research conducted and published in the 2010s. Proceeding from the west to the east part of the island, and encompassing material ranging from the 12th to the mid-fourth century BC, this study finds that, overall, the field is flourishing, despite the challenges created by the international financial crisis and the constraints posed by the global pandemic. In the last decade, the major archaeological projects which focus on Crete for the period under examination continued with their fieldwork and finds research, while new projects were also established. Additionally, as many as eight archaeological museums were opened, reopened, or are about to open. Nevertheless, final publication of large bodies of Cretan material from the period in question remain scarce, a condition which is more severe on the western half of the island. Notwithstanding its floruit, research on Early Iron Age to Classical Crete is often treated as relatively marginal, and – arguably – rather inconsequential to the grand narratives of Greek history, and art and archaeology. This paper traces the roots of this problem and shows that current work on the archaeology of Early Iron Age to Classical Crete has full potential for revolutionizing the largely Athenocentric paradigm which still pervades the study of ancient Greece.